Agresi Verbal Orang Tua dan Harga Diri Remaja: Analisis Multilevel Mengenai Dampak Name-Calling Terhadap Konsep Diri dan Harga Diri: Penelitian - Pujiyatmi, Pujiyatmi; Pamungkas, Achmad Jumeri; Hidayatulloh, M Said (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study analyzes the influence of parental verbal aggression, particularly name-calling, on adolescents' self-concept and self-esteem. Negative labeling practices are often considered minor, yet they have serious impacts on adolescent identity development. Using multilevel analysis, the study assessed the relationship between the intensity of verbal aggression, perceived family emotional support, and school social dynamics on variations in adolescent self-esteem. Data were obtained through a survey of 350 students aged 13–18 years at junior high schools in Sragen Regency and senior high schools in Karanganyar Regency, as well as in-depth interviews. The results showed that parental verbal aggression had a significant negative effect on self-concept and self-esteem (p < 0.01), while peer support moderated this effect. These findings emphasize the importance of positive communication in parenting and the need for family interventions to prevent negative self-image. Theoretically, this study enriches the psychosocial model of self-esteem formation and practically provides recommendations for counselors, educators, and parents in creating supportive communication.